2022
DOI: 10.3389/fmicb.2022.880932
|View full text |Cite
|
Sign up to set email alerts
|

wecB Gene of Salmonella Gallinarum Plays a Critical Role in Systemic Infection of Fowl Typhoid

Abstract: Salmonella enterica serovar Gallinarum (S. Gallinarum) is a host-specific pathogen causing fowl typhoid, a severe systemic infection in poultry, which leads to substantial economic losses due to high morbidity and mortality in many developing countries. However, less is known about the pathogenic characteristics and mechanism of S. Gallinarum-induced systemic infection in chickens. In this study, we deleted the S. Gallinarum UDP-N-acetylglucosamine-1-phosphate transferase gene, which contributes to the biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…(B) Spleen, the arrows show degeneration and necrosis in the white pulp. (19). In this study, in contrast, chickens infected with the mSPI-14 mutant showed no significant clinical symptoms, had a 100% survival rate, and showed no differences in gross findings and/or pathological changes compared to the uninfected group.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…(B) Spleen, the arrows show degeneration and necrosis in the white pulp. (19). In this study, in contrast, chickens infected with the mSPI-14 mutant showed no significant clinical symptoms, had a 100% survival rate, and showed no differences in gross findings and/or pathological changes compared to the uninfected group.…”
Section: Discussioncontrasting
confidence: 54%
“…To date, studies on the effects of Salmonella enterica SPI-14 on systemic infection of chickens in vivo are very limited. In our recent studies, the chickens infected with S. gallinarum WT died after showing clinical symptoms such as depression and ruffled feathers, and gross examination of the liver showed white punctate lesions and hepatomegaly ( 5 , 19 ). Furthermore, in histopathological analysis, remarkable and widespread inflammatory reactions were observed in organs, such as focal necrosis, heterophils, lymphocyte clusters in the liver, and coagulative necrosis in the spleen ( 19 ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations